AB0488 Clinical, Biological and Immunological Features of Systemic Lupus Erythematosus in A Group of Tunisian Patients. (15th July 2016) - Ben Salem, T.; Tougorti, M.; Naceur, I.; Lamloum, M.; Khanfir, M.; Ben Ghorbel, I.; Houman, M.H.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease with wild spectrum manifestations. Disease severity and outcome are variable in different ethnic groups. The aim of this study was to describe clinical, biological and immunological features of SLE in a group of Tunisian patients. Objectives: A retrospective study, including patients with SLE (Revised criteria of the American College of Rheumatology), followed in a department of Internal Medicine from 2000 to 2013. Data for demographic, clinical, biological and immunological characteristics of patients were recorded and analyzed. Treatment and outcome were described. Results: Two hundred and forty six patients with SLE were included. The sex-ratio M/F was 0.14. The mean age at the disease onset was 32.96 years (ranges 6–72 years). The mean delay to diagnosis was 20±40. 3 months. Arthralgia, arthritis and cutaneous manifestations were noted in 90.2, 46.3 and 76% of cases respectively. Pleural effusion was observed in 25.6% of cases and pericarditis in 37% of patients. Lupus nephritis was diagnosed in 104 patients (42.3%). In the 81 patients who underwent renal biopsy, class IV nephritis was the most frequent (27 cases). Neuropsychiatric manifestations were observed in 20.6% of cases and 7.3% patients had peripheral neuropathy. Biological data revealed anemia in 73.2% of cases (Among them, 83.4% had a positive Coombs test), leucopenia (44.7%), lymphopenia (78%) and thrombocytopenia in 24% of cases. Antinuclear antibodies were positive in 97.2% of cases. Anti-dsDNA antibody was positive in indirect immunofluorescence and in ELISA in 141/190 and 76/91 patients respectively. Autoantibodies to extractable nucleair antigens were positive in 165/194 cases; anti-Sm antibodies were positive in 96/152, anti-nucleosome in 26/31, anti-histone in 48/82 and anti-ribosome in 16/67 cases (they weren't systematically screened). Low rate complement was observed in 83/140 cases. Chloroquine or hydroxychloroquine were given to 234 patients and 91.4% of patients were treated with corticosteroids (mean treatment duration: 64.13±50.83 months). Immunosuppressive drugs were added in 59.3% of patients; Cyclophosphamide (n=80), Azathioprine (n=52), Methotrexate (n=11) and Mycophenolate mofetil (n=3). The mean treatment duration of immunosuppressive therapy was 37.1±33.17 months. Relapses occurred in 62.8% of cases with a mean delay of 33.4±34.45 months. Mean follow up duration was 75.65±57.26 months. Remission was noted in 133 (54%) of patients. Twenty four patients died and 43 patients were lost to follow up. End stage renal disease was observed in five patients. Infections occurred in 143 cases. SLE was associated to Sjogren syndrome (n=41), antiphospholipid syndrome (n=29), systemic sclerosis (n=10), primary biliary cirrhosis (n=5), celiac disease (n=4) and to Kikuchi disease in 3 cases. Conclusions: In our series, SLE patients had a high prevalence of cutaneous and articular manifestations. Nephritis lupus prevalence was similar to other African, Afro-american and Hispanic groups and lower than Asians. Global outcome was good with more than a half remission. Infections were frequent in our group (58%) because most of our patients had poor socio-economic conditions, in addition to their immunosuppression. Disclosure of Interest: None declared